(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article investigates the role of artistic production in historical preservation, highlighting "Flor do Deserto" from Grupo Miraira at IFCE Campus Fortaleza. The play addresses the Caldeirão da Santa Cruz do Deserto, a milestone in Ceará’s history. The research explores the cast’s prior knowledge of the Caldeirão, their interpretation of characters, and the impact of the work on public awareness of the massacre. With 44 interviewees from dance/stage and music, the study uses qualitative methodologies to understand the relationship between the performance, the cast, and historical recognition.